Symbiotic Bacteria Induced Necrotizing Pancreatitis - Verma, Rajanshu; Dhamija, Radhika; Ross, Stephen C; Batts, Donald H; Loehrke, Mark E (JOP. Journal of the Pancreas, 2010)
Context Intestinal flora and anaerobes are frequently implicated in causing infectious necrotizing pancreatitis however Bifidobacterium and Veillonella have rarely been isolated as the causative agents. Bifidobacterium and Veillonella are commensal anaerobes which reside in gastrointestinal tract and help deconjugate bile acids. Bifidobacterium is also frequently used in probiotics. Case report We present a 68-year-old man who initially presented with gallstone pancreatitis but eventually developed Bifidobacterium and Veillonella species induced necrotizing pancreatitis and pseudocyst formation. Conclusion Under rare circumstances commensal gut flora can turn pathogenic which can lead to life-threatening morbidity and may even result in mortality. Image: Necrotizing pancreatitis with air-fluid levels.